Hubungan antara Penggunaan Media Buku Cerita dengan Kemampuan Bahasa Reseptif Anak Usia Dini Umur 4-5 Tahun di TKIT Mardhatilah Kemasan Polokarto - Nafisah, Zain; Putri, Anggi Resina (Jurnal Terapi Wicara dan Bahasa, 2024)
Background: Children between the ages of 0 and 6 are called the golden years because at this age, children experience rapid development and growth in all aspects. At the age of 4-5 years, the most appropriate time to develop all abilities in children, one of the most important abilities is language. As a teacher, you can help provide stimuli such as storytelling or reading storybooks in children's language development. Objectives: To find out the relationship between the use of storybook media and the receptive language skills of children aged 4 to 5 years. Methods: This research is quantitative research that uses a correlation study research design with a cross-sectional approach. The sampling technique used is intentional sampling. The data collected will be analysed univariately and bivariately. The statistical test used is spearman rank. Results: The results of the data analysis obtained a ρ value of 0.000, which implements accepted Ha. We also know that the correlation value r = 0.668, which shows that the correlation between the two variables is strong with a positive direction. Conclusion: There is a relationship between the use of storybook media and receptive language skills with a high level of correlation and positive direction, which means that the higher the use of storybook media and the more receptive language skills are used. Keywords: Storybook media use, receptive language, preschooler, spearman rank.